AB257. The study of the influence of the changes in alpha 1-adrenergic receptor and NGF on the diabetic urethral function - Chen, Shouzhen (Transl Androl Urol, 2016)
BACKGROUND: To study the influence of the changes in the α1-adrenergic receptor and NGF/ProNGF pathway on the diabetic urethral function. METHODS: A total of 20 female Wistar rats were divided into two groups equally at random. Urethral function was examined by recordings of bladder pressure and urethral perfusion pressure (UPP). The expression of α1-adrenergic receptor in the urethra was measured via RT-qPCR and ELISA method. The expression of nerve growth factor (NGF) in the urethra was measured via RT-qPCR and ELISA method. The expression of proNGF, P75NTR and sortilin in the urethra was measured by western blotting. RESULTS: The lowest urethral pressure (UPP nadir) during urethral relaxation was higher in diabetic rats. The UPP nadir and baseline UPP in diabetic rats was significantly decreased by intravenous administration of the α1-adrenoceptor antagonist (tamsulosin). The α1a and α1d adrenergic receptor in the urethra of the diabetic group was significantly increased via RT-qPCR and western blotting (P<0.05). The RT-qPCR and ELISA studies showed a significant decrease of NGF and the western blotting studies showed a significant increase of proNGF (P<0.05). There was a statistical decrease of the P75NTR in the urethras of diabetic rats (P<0.05) and no significant difference concerning sortilin between two groups (P>0.05). CONCLUSIONS: The increase in the expression of α1-adrenoceptor and changes of the NGF/ProNGF pathway in the diabetic urethral was a possible mechanism of the diabetic urethral dysfunction.